Who is at the top? Wealth mobility over the life cycle - Stefan Hochguertel; Henry Ohlsson (Uppsala University, Department of Economics, 2012)
Who is wealthy? This paper presents empirical estimates of household movements into and out of the top percents of the wealth distribution over individual life cycles. There are life-cycle motives and precautionary motives for wealth accumulation. The opportunities to accumulate wealth create incentives for education, work effort, and entrepreneurship. We would expect considerable wealth mobility over the life cycle if the life-cycle motives and incentives to accumulate are strong and affect behavior. The data are from an administrative Swedish source that retains wealth information from tax registers. The data are unique, they follow a large sample of households over almost 40 years. There is substantial mobility when we follow individual households over long enough time spans. We find that wealth mobility increased until the end of the 1980s and then started to decrease. Age-wealth probability profiles are consistent with life-cycle motives for wealth accumulation. There are also limited precautionary motives for wealth accumulation when households experience income uncertainty.
urn:nbn:se:uu:diva-167373
Keywords: D14; D31; D91; H24; 330; intragenerational wealth mobility; wealth durations; life-cycle motives; precautionary motives; panel data; Vermögensverteilung; Lebenszyklus; Soziale Mobilität; Privater Haushalt; Schweden